A formação de professores reflexivos no contexto PIBID : uma discussão sobre as modalidades e recursos didáticos no ensino de biologia - Barreiros, Glaucia Britto (2015)
The discussion and the exchange of ideas in education courses in supervised training and instrumentation, as well as participation in incentive to teaching programs, such as PIBID does not only add experience to the curriculum of the participants, but it aims to foster construction of a reflective teaching. Understanding teaching methodologies, qualitative research, and how to reflect on the teaching practice are the basis for the choices of methods and didactic resources used in class, even in the initial training, independently, stimulating dynamic proposals in room class. However, in the training current model, the context of the discipline of supervised training are not enough to streamline the process of teaching and learning of these future teachers to a reflective teaching practice. To address the problems of a professional future in their practices, new proposals are implemented, such as PIBID project (Institutional Program of Scholarship to Initiation Teaching), in effect since 2009. Developed by HEI (Higher Education Institution), supported by the Federal government. In this sense, and in order to investigate the initial training context, this paper analyzes how undergraduates in Biology, participants of the subproject PIBID-Biology-UEM (Universidade Estadual de Maringá) understand and use in their performances the modalities and didactic resources, observing if there is a construction of reflective practice by the participants of the project. The research procedures were performed in a participatory manner, through study and reflection groups, made in the second half of 2013 until the second half of 2014, it is configured as a qualitative study of the participants. The study subjects were nineteen participants PIBID-Biology-UEM. They figured as instruments for collecting semi-structured questionnaires data, audio transcription of meetings and diaries lesson (DL). The data were submitted to Bardin content analysis (1977), that emerging a few categories, and analyzes of subcategories. Before the data was obtained the profile of the project participants that demonstrate prioritize personal issues such as commitment, curiosity and identification with the project, together with a critical look at the educational causes, with provision of research innovations and improvements to education. Participants indicate a variety of reasons to join the project, and the most cited were they like the project, the stage be paid, it is a good experience in career, the knowing the teaching and also for having participated in other projects and they do not identify. With respect to previous conceptions on the teaching methods, we found that some participants have difficulty in understanding the difference between teaching methods and teaching methodology. In conceptions on how to plan, it is said the methodology of the three pedagogical moments. In the context of DL analysis showed that although the twelve participants claim to be reflective, that reflective practice is weak. However, the actions in the project demonstrate dynamic with a plurality of modes and didactic resources, according to DL. As for the DL this does not go beyond the description of the reviews of the scenario, students, their actions and the achievement of objectives, but without the complexity of identifying failures and propose changes. Thus, the expected and necessary consideration, happens superficially in some DL. This is the core of these discussions on this research.